If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+1)+2(5-x)=3(x+5)
We move all terms to the left:
5(x+1)+2(5-x)-(3(x+5))=0
We add all the numbers together, and all the variables
5(x+1)+2(-1x+5)-(3(x+5))=0
We multiply parentheses
5x-2x-(3(x+5))+5+10=0
We calculate terms in parentheses: -(3(x+5)), so:We add all the numbers together, and all the variables
3(x+5)
We multiply parentheses
3x+15
Back to the equation:
-(3x+15)
3x-(3x+15)+15=0
We get rid of parentheses
3x-3x-15+15=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 5x+10=6x-41= | | 0.95^n=0.15 | | 51=3(27+2z) | | 3x+40=4x-6 | | 9x+10=7x+32 | | 5-x=3x | | 12b-3+6=10+20b | | 8×x/2-5/1=7x+2 | | 3×x-5=-2×4-x | | 7(x=5)=42 | | 9b–4b+3b=16 | | 4=8g-2 | | 4×1=-x+3 | | 1=p-9 | | x+10=3(x-4) | | 13x+14=3x+224 | | 4a+1/3=6a-5/7 | | 6(x-3)-2x=4(x-8) | | 7(x+3)=4x-10 | | 1=12x=-10=x | | 140=x(x+40/100) | | 7-9x=22+4x | | 5x-9=17-8x | | 3x-9=2x+16 | | 5y-12=11 | | 30m2-77m+48=0 | | -16(x+8)=4(x-42 | | (4x-7)/(4x+5)=2/3 | | 8(x-4)=-2(x+6 | | -3=-1/2x-5 | | 382000=3.82×10n | | M=95/1.5w+5 |